PENGARUH SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN PADA UD. TIMUR TERANG MAKASSAR - Dharmawaty Djaharuddin (Universitas Pandanaran, 2017)
The distribution channel is a set of grooves that followed after the product or service produced, ending in the purchase and use by end users. Volume sales are due to several factors, including: agent distribution, allocation of marketing, supply and transportation of goods. The main objective of this study was to determine which variables affect the volume of sales at UD. Timur Terang Makassar of the four variables, the distribution agent, the allocation of marketing, inventory, transportation of goods and factors among which the most predominant.This study used test method description and linear regression analysis. The results obtained demonstrate simultaneous variable distribution agent, the allocation of marketing, supply and transportation of goods significantly influence sales volume. Partially or individually variable distribution agent, marketing allocation, inventory and transportation of goods significantly influence sales volume. Among the four variables, there is one of the most dominant variables significantly affect the sales volume inventory.Key Words : Distribution Channel, Volume Sales, Regression Analyze.PENDAHULUANA.Latar BelakangPemasaran bagi setiap perusahaan merupakan suatu kebijakan dalam mencapai tujuan dan sasaran perusahaan. Setelah perusahaan menyediakan produknya dan menetapkan tempat yang tepat yang dapat dijangkau oleh para pelanggan. Demikian pula UD. Timur Terang Makassar